Optimising the focus of digital technologies in the context of implementing a sustainable development strategy for the international business environment - Olena Liutak; Оlena Baula (Економічний форум, 2024)
The active spread of digital technologies shapes the pace of dynamics and trends in the development of the international business environment: on the one hand, the flexibility of the business sphere is increasing, on the other hand, new challenges are emerging for the stability of the business environment, the competitiveness of traditional sectors of the economy, including economic and information security. The purpose of the article is to study the digital innovation activity of the business environment by comparing and modelling the impact of independent variables on the gross domestic product of the EU and Ukraine. The methodological basis used in the study was the tools of economic-mathematical and correlation analysis, comparative, quantitative, tabular analysis and synthesis, SWOT analysis. The article conducts a comparative analysis of the value of indicators of international rankings reflecting the level of digital development of the Visegrad countries and Ukraine for 2017-2023; assesses the digital and technological components of the overall international competitiveness ranking of Ukraine, Poland, the Czech Republic, Hungary and Slovakia. By using econometric analysis, the use of a linear dependence function that describes in detail the dynamics of economic development was substantiated; a multifactorial economic and mathematical model was built to determine the strength of the relationship between the indicators of digital and innovative business activity in Ukraine and the main macroeconomic indicator is GDP; a SWOT analysis of the impact of digitalisation on the achievement of global sustainable development goals by the international business environment was carried out; the directions of the new focus of digital technologies in the context of real-world development were substantiated. The practical significance of the results lies in the fact that the main scientific provisions have been brought to the level of methodological developments that can be used by: business entities – when choosing to use digital technologies, increasing their own competitiveness in the international arena; entities generating innovations – when developing digital innovations, developing innovation hubs; government authorities – when developing a regulatory framework for the implementation of digital innovations to achieve global sustainable development goals, development of digital infrastructure, and regulation of investment operations